VD_FINDINFO HC / 2022 / 66 vom 28. März 2022 - VD Tribunal cantonal (2022)
ACTION EN RESPONSABILITÉ, MANDATAIRE, DILIGENCE, FAUTE, LIEN DE CAUSALITÉ, PRINCIPE DE CAUSALITÉ, DOMMAGE, HONORAIRES | 394 CO, 397 CO, 398 al. 1 CO, 398 al. 2 CO